Unveiling the Damped Quantum Harmonic Oscillator - Efendi, Yahya; Anumillah, Faza Atika; Nurhuda, Muhammad (Jurnal Kumparan Fisika, 2024)
Abstract   This article dis cusses the often-overlooked "damped" quantum harmonic oscillator, a vibrating system that loses energy over time. We bridge the classical-quantum divide, starting with the familiar equation of motion for a damped oscillator using Hooke's law. Delving into quantum mechanics, we explore how the Schrödinger equation governs its behavior. We then chart a path to understanding its energy changes and time evolution using mathematical tools like annihilation and creation operators, eigenstates, and eigenvalues. We then step through the understanding of its energy changes and time evolution using mathematical tools like annihilation and creation operators, eigenstates, and eigenvalues. Finally, we introduce the time-dependent Schrödinger equation for a damped quantum harmonic oscillator, which paves the way for stable oscillations   Keywords: Damped Quantum Oscillator; Canonical Quantization; Invariant Operator; Time-Dependent Schrödinger Equation   Abstrak   Artikel ini membahas osilator harmonik kuantum teredam, sebuah sistem getaran yang kehilangan energi seiring waktu, yang sering kali diabaikan dalam kajian fisika. Kami menjembatani kesenjangan antara mekanika klasik dan kuantum, dimulai dengan persamaan gerak osilator teredam berdasarkan hukum Hooke. Dalam ranah mekanika kuantum, kami mengeksplorasi bagaimana persamaan Schrödinger mengatur perilaku sistem ini. Selanjutnya, kami menelusuri perubahan energi dan evolusi waktu osilator ini menggunakan alat matematika seperti operator annihilasi dan kreasi, eigenstate, dan eigenvalue. Terakhir, kami memperkenalkan persamaan Schrödinger bergantung waktu untuk osilator harmonik kuantum teredam, yang membuka wawasan terhadap osilasi stabil dalam sistem ini.   Kata kunci: Osilator Kuantum Teredam; Kuantisasi Kanonik; Operator Invarian; Persamaan Schrödinger Bergantung Waktu